Public Perception About Ecosystem Maninjau Due Keramba cage (KJA) in the Kecamatan Tanjung Raya Kabupaten Agam. - Noviyanto, Irfan - (Pendidikan Geografi, 2014)
This study aimed to obtain and analyze the data or in-depth information about Public Perceptions About Ecosystem Maninjau Due Keramba cage (KJA) in the Kecamatan Tanjung Raya Kabupaten Agam.The research is a qualitative approach that would reveal the Public Perception About Ecosystem Maninjau Due Keramba cage (KJA) in the district of Tanjung Raya Agam. Informants were taken by using purposive sampling which consists of communities in Muko-Muko Kanagarian and Kenagarian Bayur in Tanjung Raya Agam. The research that researchers do is in terms of: 1) Public perception of Keramba cage, 2) How is the public perception of water, silting, and fish endemic to the lake Maninjau, 3) How is the public perception of the role of the Government of the lake ecosystem Maninjau.Results of the study found that: 1) floating net cages located in Tanjung Raya Maninjau lake Agam has exceeded the limit. Where every citizen has approximately two floating net cages. Causing pollution to the lake. 2) the state of the water in the lake has been polluted Maninjau this is evidenced from the color of the muddy water and washing water will be as white as rice in the morning, and the water smells like the smell of fish carcasses. 3) government in the District Kanjung Kingdom Agam less oversee the activities Keramba cage (KJA) in lake Maninjau, it is seen from the state of the lake Maninjau increasingly more severe the condition was. Regulations made by the Government does not work in practice. And the lack of rules to be farmed.